Kegagalan Bangunan dari Sisi Industri Konstruksi - Hermanto, Eddy; Kistiani, Frida (MEDIA KOMUNIKASI TEKNIK SIPIL, 2006)
There are plenty of buildings faliured in Indonesia until now. The process of collapse was caused of redistribution of moment happened in its structure not like its structural design. Building failured can be happened and caused by human activities, nature behavioral characteristic and combination of them. Refer the structural aspect, structural system is the first and prime element of building that supported building forever where man to live in. There must have strong efforts to analyze structural system as a whole building to provide safety factor, especially before construction have done. The point of view can be explained in planning, architectural design, engineering, economics, and environment. The last factor to avoid building failure consist of people or public participation and regulation of inspection periodically must be involved in building development processed. Keywords: building failure, redistribution of momentPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3933[How to cite: Hermanto, E. dan Kistiani, F., 2006, Kegagalan Bangunan dari Sisi Industri Konstruksi, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 1, pp. 48-55]